2006
DOI: 10.1002/lapl.200610033
|View full text |Cite
|
Sign up to set email alerts
|

Applications of laser-induced fluorescence spectroscopy for the determination of NADH in experimental neuroscience

Abstract: There is an increasing need for continuously monitoring changes in brain metabolism and neuronal activity, respectively. The aim is to improve our understanding of mechanisms involved in physiological as well as pathophysiological and behavioural responses and to characterise drug actions. Changes of NADH concentration in the brain can be regarded as an index of changes in mitochondrial activity, which is closely related to neuronal activity. During the last decade the determination of NADH fluorescence by las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Concentrations of nicotinamide adenine dinucleotide (NADH), a cosubstrate for energy transfer in the respiratory chain, mirror mitochondrial oxidative metabolism in vitro (Shuttleworth et al, 2003) as well as in vivo (Ince et al, 1992; Rex et al, 1999). Determination of changes in NADH fluorescence, reflecting changes in CNS metabolism with high spatial and time resolution using laser‐induced fluorescence spectroscopy in vivo, is an established method (Mottin et al, 2003; Rex and Fink, 2006a, b). Therefore, this technique was used to measure metabolic activity, indicating changes in neuronal activity.…”
mentioning
confidence: 99%
“…Concentrations of nicotinamide adenine dinucleotide (NADH), a cosubstrate for energy transfer in the respiratory chain, mirror mitochondrial oxidative metabolism in vitro (Shuttleworth et al, 2003) as well as in vivo (Ince et al, 1992; Rex et al, 1999). Determination of changes in NADH fluorescence, reflecting changes in CNS metabolism with high spatial and time resolution using laser‐induced fluorescence spectroscopy in vivo, is an established method (Mottin et al, 2003; Rex and Fink, 2006a, b). Therefore, this technique was used to measure metabolic activity, indicating changes in neuronal activity.…”
mentioning
confidence: 99%
“…The time course of the NADH absorption in vitro was determined by the NADH fluorescence measurement continuously using the laser-induced fluorescence spectroscopy (4,35). In the preceding experiment we could show that the fluorescence intensity and the concentration of NADH in an aqueous solution are closely and directly proportional and therefore even quantification of the NADH absorbed was possible.…”
Section: Discussionmentioning
confidence: 98%
“…Mitochondrial dysfunction may cause or is involved in many pathological states like common neurodegenerative diseases (1,2). Consequently, in vitro and in vivo measurement of NADH fluorescence is a well established method to evaluate mitochondrial function in the brain (for review see (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Their cellular concentration can be measured by laser-induced fluorescence techniques. Rex et al [9] showed that these compounds are ideal indicators to assess the mitochondrial metabolism activity and that changes in the concentrations reflect an index of mitochondrial activity. However the release of the produced energy is coupled to the translocalisation of protons from the sub-cellular matrix to the outer side of the mitochondrial membrane.…”
Section: Discussionmentioning
confidence: 99%